THE ROLE OF BRUCELLA VIRULENCE PROTEINS IN SUBVERSION OF HOST INNATE IMMUNE DEFENSES - Girish K Radhakrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Brucella spp. are infectious intracellular bacterial pathogens found in a wide range of mammals, includinghumans, causing abortion, infertility and undulant fever. Brucellaereplicate primarily in macrophages and dendritic cells and the mechanisms by which brucellae manipulate the intracellular milieu for theirsurvival remain poorly understood. Brucellaspp. are considered as stealth pathogens as they efficiently evade or suppress host immune responses for their chronic persistence in the host. Identification and characterization of some of the virulence proteins of brucellae have gainedinsights on how brucellaemodulate the host immune responses for their survival. This review focuses on the modulation of host innate immune responses by the identified virulence proteins of  Brucellaspp.